Evaluation of Hypogammaglobulinemia in Chronic Lymphocytic Leukemia Patients and Its Relation to Poor Prognostic Factors - (:unkn) unknown (GALENOS YAYINCILIK, 2018)
Aim: Chronic lymphocytic leukemia (CLL) is a heterogenous disease with variable clinical course. Rai staging system is used for at least 40 years to predict prognosis and need for treatment but more prognostic factors are needed. Infections have been known to have a significant impact on patients with CLL. It is postulated that hypogammaglobulinemia accounts for the high infection rate. The severity of hypogammaglobulinemia is correlated with disease stage and duration. Methods: Data of patients who were diagnosed with CLL according to the the National Cancer Institute Working Group criteria were analyzed retrospectively. The patients were classified according to absolute lymphocyte count, immunoglobulin (Ig) levels, Rai stage, organomegaly, mass lymphadenopathy, lymphocyte doubling time (LDT), presence of B symptoms and treatment status. Results: We found that low IgA levels were associated with LDT and splenomegaly indicating disease burden and activity. The patients with low IgA and IgM levels received more treatment than others with normal Ig levels. Conclusion: In our study, we could not find a significant relationship between the stage and Ig levels but low IgA and IgM levels were significantly associated with need for treatment. Therefore, we suggest measuring IgA and IgM levels which is a simple and inexpensive test, to predict which patients may need treatment and should be observed closely.
Keywords: Chronic lymphocytic leukemia; hypogammaglobulinemia; chronic lymphocytic leukemia prognosis; immunoglobulins; IN-SITU HYBRIDIZATION; CD38 EXPRESSION; SCORING SYSTEM; GENE MUTATION; DIAGNOSIS; LYMPHOMA; CLL; INFECTIONS; GUIDELINES; FEATURES